Criação, desenvolvimento e análise das propriedades de medida da escala de medo de retorno ao esporte na população brasileira - SANTOS, Artur Eduardo Kalatakis dos (2022)
INTRODUCTION: Several factors that can influence the athlete's recovery, including fear. Psychological factors play a role in increasing recovery time, and there may be a disconnect between the initial condition and treatment adherence. Thus, psychological factors are important predictors of recovery and high performance return to sport. OBJECTIVE: The aim of this study was to create, develop and validate the Fear of Return to Sport Scale (FRESS) for the Brazilian population in order to measure the fear of returning to sport. METHODS: This is a questionnaire validation study including 192 participants. To determine the content validity, 8 experts in the field of sport and injury were consulted, and the coefficient of content validity was used. To identify and guarantee the unidimensionality of the FRESS, exploratory factor analysis (EFA) was used, followed by confirmatory factor analysis (CFA). The following fit indices for model acceptability were considered: root mean square error of approximation (RMSEA), comparative fit index (CFI), Tucker-Lewis index (TLI), standardized root mean square residual (SRMR), and chi-square /degrees of freedom (DF). To determine the construct validity, Spearman's correlation coefficient (rho) was used to correlate the FRESS score with the scores of the questionnaires already validated for the Brazilian population: Numerical Pain Scale (NPS), Catastrophic Thoughts about Pain Scale (CTPS), Self-Estimated Functional Inability because of the Pain Questionnaire (SEFIP- sport), and Hospital Anxiety and Depression Scale (HADS). Internal consistency was calculated using Cronbach's alpha and test-retest reliability was calculated using the intraclass correlation coefficient (ICC). In addition, ceiling and floor effects were calculated and will be evaluated in this study. RESULTS: Initially, 25 questions were proposed to measure the fear of returning to sport for injured athletes. Of these 25 questions, 4 questions were excluded due to similarity to other questions. After applying the content validity coefficient, 8 questions were excluded for presenting a value lower than 0.80. Therefore, the FRESS version after content validity had 13 questions. This 13-item structure presented a domain in the EFA. However, in the CFA, 5 items were excluded for presenting high covariance with the error of several other FRESS items. Thus, the structure of the FRESS was tested with a domain and 8 items, and adequate fit indices were observed: chi- square/DF = 1.75, TLI = 0.990, CFI = 0.986, RMSEA (90% confidence interval) = 0.068 (0.027 to 0.104) and SRMR = 0.041. Regarding construct validity, we observed a magnitude of correlation varying between 0.470 and 0.257, as expected, with NPS, CTPS, anxiety and depression domains of the HADS, and SEFIP-sport. Internal consistency (Cronbach's alpha = 0.868) and reliability (ICC = 0.896) were considered adequate. Ceiling and flower effects were not observed. CONCLUSION: The FRESS with one domain and eight items has acceptable measurement properties, and its use in the clinical and sporting environment to measure the fear of returning to sport in injured athletes is supported.